Implementation of Evidence-Based Nursing Practice through the Education and Aerobic Movement to Burn Blood Sugar (GEROBAK BALADA) Intervention in Clients with Diabetes Mellitus and Obesity - Rodiah Pulungan; Nurhayati Nurhayati; Dewi Anggraini (GLOBAL HEALTH SCIENCE GROUP, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease whose prevalence continues to increase both globally and nationally, and is commonly experienced by women with obesity. Community-based non-pharmacological interventions that focus on education and physical activity are needed to support the management of this disease. One approach used is the implementation of Evidence-Based Nursing Practice (EBNP) through the Education and Aerobic Movement to Burn Blood Sugar (Gerobak Balada) program. This study aims to analyze the effect of the Gerobak Balada intervention on reducing blood glucose levels in clients with diabetes mellitus and obesity. This is a quasi-experimental pre-post study with an intervention group. The intervention was delivered over 12 sessions between October and December 2024 to 31 DM clients in Rawasari Subdistrict using purposive sampling technique. Data were collected using instruments including random blood glucose (RBG) measurements with Codefree test strips, questionnaires on knowledge, behavior, and frequency of treatment visits. Data were analyzed using paired t-tests. A significant reduction was observed in RBG levels from 304.39 ± 68.10 mg/dL to 236.45 ± 60.72 mg/dL (p < 0.001). There were also significant increases in knowledge scores (from 69.90 to 85.68; p < 0.001), behavior scores (from 66.81 to 77.03; p < 0.001), and treatment visit frequency (from 1.68 to 2.16 times; p = 0.023). The implementation of Gerobak Balada proved effective in lowering blood glucose levels and improving knowledge, healthy behavior, and medication adherence in clients with diabetes and obesity. This intervention supports the EBNP approach and has the potential to be integrated into community-based DM prevention programs.